Whole blood interferon-γ release assay is a useful tool for the diagnosis of tuberculosis infection particularly among Bacille Calmette Guèrin-vaccinated children - Tsolia, M. N.; Mavrikou, M.; Critselis, E.; Papadopoulos, N. G.; Makrinioti, H.; Spyridis, N. P.; Metsou, F.; Tsagaraki, M.; Koulouri, M.; Kafetzis, D. A. (Pediatr Infect Dis J, 2010)
The performance of QuantiFERON-tuberculosis (TB) Gold-In-Tube assay was compared with the tuberculin skin test for the diagnosis of TB among children. It was shown that among non-Bacille Calmette Guèrin immunized children, agreement between tests was excellent both in those with TB disease and in TB contacts. Among Bacille Calmette Guèrin-immunized children, agreement was fair in those with active disease and poor among TB contacts. It is concluded that QuantiFERON-TB Gold-In-Tube compares with the tuberculin skin test in the diagnosis of TB disease and latent tuberculosis infection in TB contacts among children and has enhanced specificity.
Keywords: Adolescent BCG Vaccine Blood Cells; Cultured Child Child; Differential Humans Infant Infant; Newborn Interferon-gamma Sensitivity and Specificity Tuberculin Test Tuberculosis; Preschool Diagnosis